Young people with learning disabilities who sexually abuse: understanding, identifying and responding from within generic education and welfare services - Fyson, Rachel (Russell House Publishing, 2007)
This chapter will start by providing an overview of current knowledge about young people with learning disabilities who sexually abuse. Research cited will, unless otherwise indicated, be limited to UK studies since international variations in the definitions of both learning disability and sexual abuse make the use of a wider literature base problematic – particularly that relating to prevalence and incidence. It will then go on to report key findings from a recent study (Fyson et al, 2003; Fyson, 2005) which examined how special schools and statutory child protection and youth offending services in four English local authorities responded to sexually inappropriate or abusive behaviours exhibited by young people with learning disabilities. It will conclude by highlighting areas of current practice which give cause for concern, and suggest some pointers for future best practice.